First you need to add each and everyone of the seats in the plane so
14 + 64 + 108 = 186
Then divide 186 by 2 to determine the half
And that is 93
Then multiply each by the seats so
5/7 * 14 = 10
5/16 * 64 = 20
5/9 * 108 = 60
Then you add everything and it’s equals to 90 and since it’s below 93 half of the seats aren’t being used
Hope this helps!
<u>Answer:</u>
<em>First Equation → </em><u><em>y = 21/4</em></u>
<em>Second Equation → </em><u><em>x = -1/57</em></u>
<u />
<u>Explanation:</u>
<em>solving equation #1</em>
<em></em>
step 1 - simplify
<em></em>
![\displaystyle\frac{1}{6}y - \displaystyle\frac{1}{2} = 3 - \displaystyle\frac{1}{2}y\\\\\displaystyle\frac{1}{6}* \displaystyle\frac{y}{1} - \displaystyle\frac{1}{2} = 3 - \displaystyle\frac{1}{2}* \displaystyle\frac{y}{1}\\\\\displaystyle\frac{y}{6} - \displaystyle\frac{1}{2} = 3 - \displaystyle\frac{y}{2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cfrac%7B1%7D%7B6%7Dy%20-%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B2%7D%20%3D%203%20-%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B2%7Dy%5C%5C%5C%5C%5Cdisplaystyle%5Cfrac%7B1%7D%7B6%7D%2A%20%5Cdisplaystyle%5Cfrac%7By%7D%7B1%7D%20%20-%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B2%7D%20%3D%203%20-%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B2%7D%2A%20%5Cdisplaystyle%5Cfrac%7By%7D%7B1%7D%5C%5C%5C%5C%5Cdisplaystyle%5Cfrac%7By%7D%7B6%7D%20-%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B2%7D%20%3D%203%20-%20%5Cdisplaystyle%5Cfrac%7By%7D%7B2%7D)
step 3 - multiply each side of the equation by six
![\displaystyle\frac{y}{6} - \displaystyle\frac{1}{2} = 3 - \displaystyle\frac{y}{2}\\\\\displaystyle\frac{y}{6} * \displaystyle\frac{6}{1}- \displaystyle\frac{1}{2} * \displaystyle\frac{6}{1}= \displaystyle\frac{3}{1} *\displaystyle\frac{6}{1} - \displaystyle\frac{y}{2}* \displaystyle\frac{6}{1}\\\\y - 3 = 18 - 3y](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cfrac%7By%7D%7B6%7D%20-%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B2%7D%20%3D%203%20-%20%5Cdisplaystyle%5Cfrac%7By%7D%7B2%7D%5C%5C%5C%5C%5Cdisplaystyle%5Cfrac%7By%7D%7B6%7D%20%2A%20%5Cdisplaystyle%5Cfrac%7B6%7D%7B1%7D-%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B2%7D%20%2A%20%5Cdisplaystyle%5Cfrac%7B6%7D%7B1%7D%3D%20%5Cdisplaystyle%5Cfrac%7B3%7D%7B1%7D%20%2A%5Cdisplaystyle%5Cfrac%7B6%7D%7B1%7D%20-%20%5Cdisplaystyle%5Cfrac%7By%7D%7B2%7D%2A%20%5Cdisplaystyle%5Cfrac%7B6%7D%7B1%7D%5C%5C%5C%5Cy%20-%203%20%3D%2018%20-%203y)
step 4 - add three to both sides of the equation.
![y - 3 = 18 - 3y\\\\y-3+3=18+3-3y\\\\y = -3y+21](https://tex.z-dn.net/?f=y%20-%203%20%3D%2018%20-%203y%5C%5C%5C%5Cy-3%2B3%3D18%2B3-3y%5C%5C%5C%5Cy%20%3D%20-3y%2B21)
step 5 - add three y to both sides of the equation.
![y = -3y+21\\\\y+3y = -3y+3y+21\\\\y+3y=21](https://tex.z-dn.net/?f=y%20%3D%20-3y%2B21%5C%5C%5C%5Cy%2B3y%20%3D%20-3y%2B3y%2B21%5C%5C%5C%5Cy%2B3y%3D21)
step 6 - simplify
![y+3y=21\\\\4y=21](https://tex.z-dn.net/?f=y%2B3y%3D21%5C%5C%5C%5C4y%3D21)
step 7 - divide both sides of the equation by four
![4y=21\\\\\displaystyle\frac{4y}{4} = \displaystyle\frac{21}{4}\\ \\y = \displaystyle\frac{21}{4}](https://tex.z-dn.net/?f=4y%3D21%5C%5C%5C%5C%5Cdisplaystyle%5Cfrac%7B4y%7D%7B4%7D%20%3D%20%5Cdisplaystyle%5Cfrac%7B21%7D%7B4%7D%5C%5C%20%5C%5Cy%20%3D%20%5Cdisplaystyle%5Cfrac%7B21%7D%7B4%7D)
Therefore, the solution to the first given equation is <u><em>y = 21/4 </em></u><em>or y = 5.25.</em>
<u><em /></u>
<em>solving equation #2</em>
<em />
step 1 - simplify.
![4x + \displaystyle\frac{1}{15} = \displaystyle\frac{2x}{10} \\\\4x + \displaystyle\frac{1}{15} = 2*\displaystyle\frac{x}{10}\\\\4x+\displaystyle\frac{1}{15} = \displaystyle\frac{x}{5}](https://tex.z-dn.net/?f=4x%20%2B%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B15%7D%20%20%3D%20%5Cdisplaystyle%5Cfrac%7B2x%7D%7B10%7D%20%5C%5C%5C%5C4x%20%2B%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B15%7D%20%20%3D%202%2A%5Cdisplaystyle%5Cfrac%7Bx%7D%7B10%7D%5C%5C%5C%5C4x%2B%5Cdisplaystyle%5Cfrac%7B1%7D%7B15%7D%20%20%3D%20%5Cdisplaystyle%5Cfrac%7Bx%7D%7B5%7D)
step 2 - multiply each side of the equation by five.
![4x+\displaystyle\frac{1}{15} = \displaystyle\frac{x}{5}\\\\\displaystyle\frac{4x}{1}* \displaystyle\frac{5}{1} +\displaystyle\frac{1}{15} * \displaystyle\frac{5}{1} = \displaystyle\frac{x}{5}* \displaystyle\frac{5}{1} \\\\20x + \displaystyle\frac{1}{3} = x](https://tex.z-dn.net/?f=4x%2B%5Cdisplaystyle%5Cfrac%7B1%7D%7B15%7D%20%20%3D%20%5Cdisplaystyle%5Cfrac%7Bx%7D%7B5%7D%5C%5C%5C%5C%5Cdisplaystyle%5Cfrac%7B4x%7D%7B1%7D%2A%20%5Cdisplaystyle%5Cfrac%7B5%7D%7B1%7D%20%20%2B%5Cdisplaystyle%5Cfrac%7B1%7D%7B15%7D%20%2A%20%5Cdisplaystyle%5Cfrac%7B5%7D%7B1%7D%20%20%3D%20%5Cdisplaystyle%5Cfrac%7Bx%7D%7B5%7D%2A%20%5Cdisplaystyle%5Cfrac%7B5%7D%7B1%7D%20%5C%5C%5C%5C20x%20%2B%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B3%7D%20%3D%20x)
step 3 - subtract twenty x from each side of the equation.
![20x + \displaystyle\frac{1}{3} = x \\\\20x -20x+ \displaystyle\frac{1}{3} = x -20x\\\\\displaystyle\frac{1}{3} = -19x](https://tex.z-dn.net/?f=20x%20%2B%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B3%7D%20%3D%20x%20%5C%5C%5C%5C20x%20-20x%2B%20%5Cdisplaystyle%5Cfrac%7B1%7D%7B3%7D%20%3D%20x%20-20x%5C%5C%5C%5C%5Cdisplaystyle%5Cfrac%7B1%7D%7B3%7D%20%3D%20-19x)
step 4 - divide each side of the equation by negative nineteen.
![\displaystyle\frac{1}{3} = -19x\\\\\displaystyle\frac{\displaystyle\frac{1}{3} }{-19} = \displaystyle\frac{-19x}{-19} \\\\-\displaystyle\frac{1}{57} = x](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cfrac%7B1%7D%7B3%7D%20%3D%20-19x%5C%5C%5C%5C%5Cdisplaystyle%5Cfrac%7B%5Cdisplaystyle%5Cfrac%7B1%7D%7B3%7D%20%7D%7B-19%7D%20%3D%20%5Cdisplaystyle%5Cfrac%7B-19x%7D%7B-19%7D%20%5C%5C%5C%5C-%5Cdisplaystyle%5Cfrac%7B1%7D%7B57%7D%20%3D%20x)
step 5 - switch
![-\displaystyle\frac{1}{57} =x\\\\x = -\displaystyle\frac{1}{57}](https://tex.z-dn.net/?f=-%5Cdisplaystyle%5Cfrac%7B1%7D%7B57%7D%20%20%3Dx%5C%5C%5C%5Cx%20%3D%20-%5Cdisplaystyle%5Cfrac%7B1%7D%7B57%7D)
Therefore, the solution to the second equation is <em><u>x = -1/57.</u></em>
Answer:
360 degrees
Step-by-step explanation:
Answer:
sqrt166, 13, 14
Step-by-step explanation: